Sanksi Pidana terhadap Anak yang Melakukan Tindak Pidana Kekerasan Dalam Rumah Tangga - Pius. A. Samponu; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2022)
As a result of early marriage that takes place without the mental readiness of the partner, it ends in divorce and also triggers domestic violence. The purpose of this research is to analyze the legal arrangements for domestic violence crimes and to examine criminal sanctions against minors who commit domestic violence crimes. The research methods used include normative research methods using a statutory approach, and a conceptual approach. Primary data is sourced from legislation relevant to the problem being studied, while secondary data and tertiary data are sourced from books, legal journals and legal websites related to the problem. The result shows that the regulation regarding domestic violence is contained in Law Number 23 of 2004, the definition of domestic violence is any form of physical, psychological, sexual violence, and neglect of the household and is classified as against the law that occurs in the household environment and causes suffering to the victim. Protection for victims of domestic violence begins with protection by the police, health sector, social worker sector, companion volunteers, spiritual mentors, advocacy protection, and protection from judicial institutions. Domestic violence committed by children due to the phenomenon of early marriage, efforts to protect legal rights refer to the child protection law Law Number 17 of 2016 and Law Number 11 of 2012 concerning the Child Criminal Justice System with imprisonment or job training.